Cryosphere-fed irrigation networks in the northwestern Himalaya: precarious livelihoods and adaptation strategies under the impact of climate change - Nüsser, Marcus; Dame, Juliane; Parveen, Sitara; Kraus, Benjamin; Baghel, Ravi; Schmidt, Susanne (Mountain research and development, 2019)
Irrigated agriculture is crucial for the livelihood security of mountain communities in the northwestern part of the Himalayan arc and adjoining regions of the Karakoram Hindu Kush and Trans-Himalaya. Using meltwater from glaciers, snow, and permafrost, mountain dwellers have developed sophisticated techniques to cope with recurrent water scarcity caused by glacier retreat, glacier thinning, and seasonal snow-cover dynamics. Based on case studies from the Nanga Parbat region, Hunza-Karakoram, and Ladakh, this paper seeks to identify general patterns and site-specific characteristics of agrarian practices and adaptation strategies in the face of climate change. The comparative case study approach reveals differing responses to water scarcity, which depend on local conditions and include the construction of new irrigation channels, installation of pipes, and building of artificial ice reservoirs. The biophysical investigation is supplemented by an exploration of socioeconomic factors and is based on long-term research in the 3 study areas. The methods used include multitemporal remote sensing analysis, mapping of natural water storage components and irrigation infrastructure, and interviews. Taking into consideration social factors such as the expansion of off-farm income opportunities and market integration, we identify key variables that affect the sustainability and resilience of land use systems. Outcomes are diverse, ranging from the intensification and extension of irrigated mountain agriculture to the abandonment of irrigated areas, depending on local sociohydrological settings.